The Authority of Judges in The Application of Restorative Justice for Children in Indonesia - Dewi, Riska Ameliana; Aprilianda, Nurini; Mulyono, Bambang Hery; Priadi, Randy Hilman (Jurnal Hukum dan Peradilan, 2025)
This study aims to analyze the authority of judges in applying the principle of restorative justice in cases involving children in conflict with the law and the obstacles to its implementation. The research approach uses a normative legal method with a legislative, conceptual, and case approach. Secondary data were collected through a review of six main laws, eight court decisions, and twenty-five related academic sources, then analyzed qualitatively using deductive reasoning. The results show that the authority of judges in applying restorative justice is based on the value of substantive justice as stipulated in Supreme Court Regulation Number 1 of 2024. However, its implementation is still hampered by regulatory inconsistencies between law enforcement agencies, a low level of understanding among officials and the public, and the absence of uniform technical guidelines. This study emphasizes the need for regulatory synchronization and capacity building among officials to ensure the effective and fair implementation of restorative justice oriented towards the best interests of children in Indonesia.